PHYSICAL MODEL OF THE INTERACTION OF AIR STREAMS WITH A FLAT SURFACE RELIEF - PUNDYK, SERHII; KARMALITA, ANATOLII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article examines the method of controlling the position of flat parts of shoes, which have asymmetry of surface roughness, with the help of air jets. Currently, a large number of natural and artificial materials are used in shoe production, the surfaces of which are not smooth, but have irregularities, the parameters of which are different on the front and back surfaces of these materials. All surfaces of parts, depending on the material, method and technological process of their production, have different roughness. Studying the possibility and conditions of determining the position of flat parts of shoes made of such materials according to the "front side - back side" feature using air jets is difficult, first of all, due to the great variety of irregularities, which, in turn, arises due to the variety of methods of obtaining them, different technological or operational purposes. In this connection, there is a need to typify these surfaces. Most shoe materials have a different topography of opposite surfaces. The proposed typification of surfaces by the nature of the directions and profiles of irregularities creates a certain model of the surface topography, which determines the type of air flow around the surface and protrusions of irregularities. To analyze the interaction of air jets with the surface of a flat part, it is considered as a stationary body placed in an air stream impinging on it. Air flow is characterized by a speed that can change from point to point when flowing around the body. The force acting on a flat part is formed due to the fact that it, slowing down the air flow, takes part of this energy. A 3D model of the device was created in the SolidWorks software environment and a simulation of the process of interaction of air jets with the surfaces of parts having different topographies was carried out in the SolidWorks Flow Simulation program.
Keywords: typification of irregularities; macro-irregularities; pressure; air jets